A new method for predicting the oil displacement volume by waterflood huff-puff of the fractured-cavity type carbonate oil reservoirs - Peng, Cao; Peng, Wang; Zhiliang, Liu; Jiajun, Chen; Guohui, Li; Yifan, Du (Frontiers in Energy Research, 2024)
Introduction: More than two billion tons of oil reserves have been discovered in the fractured-cavity type carbonate reservoirs in Tarim Basin, which is a key field for increasing reserves and production in the future. This type of oil reservoirs is characterized by extremely high heterogeneity, and waterflood huff-puff oil displacement is generally used for secondary development of the oil reservoirs. The conventional methods are dominated by qualitative evaluation, which are insufficient to predict the oil production increase by waterflood huff-puff in various karst zones. Methods: The new method developed in this study involves four aspects, i.e., establishing a standard well database, optimally selecting the key development indicators, equivalent classification of reservoir space type, and optimally selecting the classification and evaluation methods for oil production increase by waterflood huff-puff. From the perspective of reservoir space type, the result of waterflood huff-puff oil displacement of multi-cave type reservoir (large scale) is better than that of relatively isolated cave type reservoir, followed by the fractured-vuggy type reservoir. Results and discussion: The new method shows advantages in the following aspects: 1) The differences in reservoir geological genesis and spatial structure characteristics in various karst zones are involved; 2) The difference in internal filling features of the same type of reservoir is integrally determined based on the changes in production performance; 3) The actual development characteristics of waterflood huff-puff oil displacement wells in various karst zones are systematically analyzed, and the criteria for selecting standard wells is formulated; 4) The violin plot is introduced as the main study tool for predicting and discriminating oil production increase by waterflood huff-puff displacement. Therefore, the new method is more capable of predicting the oil production increase by waterflood huff-puff in various karst zones.